1987
DOI: 10.1111/j.1748-1716.1987.tb08273.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and neuroendocrine responses of piglets to hypoxia during postnatal development

Abstract: Breathing response to 12% and 6% O2 in N2 (at isocapnia) was measured in anaesthetized piglets, 1-5 and 19-25 days old, before and after 3 mg kg-1 i.v. naltrexone. The degree of interaction between the anaesthetic and naltrexone was assessed. At the end of each hypoxic trial, arterial blood was sampled for measurements of pH and gas tensions, (Met)enkephalin-Arg6-Phe7, adenosine, noradrenaline and adrenalin. Whereas respiration in older animals was stimulated by hypoxia, young piglets had a biphasic response w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The baseline levels of VT and RF, blood gases, ABP and HR recorded in the 3-day-old, Saffan-anaesthetized piglets of the present study were comparable to those recorded by others in conscious or lightly sedated piglets of a similar age (Darnall, 1985;Moss, Runold, Dahlin, Fredholm, Nyberg & Lagercrantz, 1987;Darnall et al 1991;Rosen, Schecter, Mellins & Haddad, 1993). The levels of P°and ABP were markedly lower than those expected in adult mammals, but well within the range expected in a newborn mammal.…”
Section: Responses Evoked In Newborn Pigletsmentioning
confidence: 50%
“…The baseline levels of VT and RF, blood gases, ABP and HR recorded in the 3-day-old, Saffan-anaesthetized piglets of the present study were comparable to those recorded by others in conscious or lightly sedated piglets of a similar age (Darnall, 1985;Moss, Runold, Dahlin, Fredholm, Nyberg & Lagercrantz, 1987;Darnall et al 1991;Rosen, Schecter, Mellins & Haddad, 1993). The levels of P°and ABP were markedly lower than those expected in adult mammals, but well within the range expected in a newborn mammal.…”
Section: Responses Evoked In Newborn Pigletsmentioning
confidence: 50%
“…There may be other neurochemicals, such as adenosine, opioids, and prostaglandins, that play a role in the ventilatory response to hypoxia during development (11,37). Adenosine is an inhibitory amino acid that has been shown to depress respiration in early life.…”
Section: Discussionmentioning
confidence: 99%
“…Although catecholamines have been shown to affect respiration via peripheral chemosensory mechanisms [18], the presence of dopamine and norepinephrine cell bodies in the brainstem suggests a central respiratory control mechanism involving these neurotransmitters [19]. McCrimmon and Lalley [20] showed that clonidine, an · 2 -adrenergic agonist, decreased phrenic nerve activity in chloralose-anesthetized cats, in which the peripheral ventilatory input was removed by sectioning the vagus, aortic and carotid sinus nerves.…”
Section: Discussionmentioning
confidence: 99%